La justicia restaurativa establecida en la Ley 906 de 2004 frente al fin del proceso penal (2012)
Colombia has gone through a series of transformations in regards of justice administration all of them aimed at improving the access to the processes and their celerity. Regarding the criminal system, it was proposed to implement an accusatory system, which has given rise to new measures that have generated discussion. One of them, maybe the one that has been more debated in the academic field, is the principle of opportunity, which grants judges with a high level of discretion when it comes to the practice of criminal law. This paper analyzes if restorative justice, established by Law 906 of 2004, achieves to settle the social conflict generated by crime, as was proposed by the criminal process of the social and democratic Rule of Law. For that purpose this paper turned to a documental study and to the finalistic theory of law.